2018
DOI: 10.1155/2018/2654572
|View full text |Cite
|
Sign up to set email alerts
|

Local Treatment of Metastatic Prostate Cancer: What is the Evidence So Far?

Abstract: Background Advances in technological, laboratorial, and imaging studies and new treatments available in the last decades significantly improved prostate cancer survival rates. However, this did not occur in metastatic prostate cancer (mPCa) at diagnosis which, in young and fit patients, will become invariably resistant to the established treatments. Progression will lead to an impairment in patients' quality of life and disease-related death. Methods The authors intend to perform a literature review of the adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Prostate cancer (PC) is the most commonly diagnosed non-cutaneous tumor in men and the second leading cause of male cancer-related deaths in Western society [1]. This cancer is often characterized by a slow and symptom-free growth, and early-stage treatments include radical prostatectomy, novel androgen receptor (AR) pathway inhibitors, such as abiraterone and enzalutamide, external beam radiotherapy (RT), brachytherapy and cryotherapy [2,3]. Further, use of new tracers for Positron Emission Tomography/Computed Tomography (PET/TC) [4,5,6,7] and novel focal therapies [8,9] have provided important advances in diagnosis, follow-up and treatment of PC patients in the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…Prostate cancer (PC) is the most commonly diagnosed non-cutaneous tumor in men and the second leading cause of male cancer-related deaths in Western society [1]. This cancer is often characterized by a slow and symptom-free growth, and early-stage treatments include radical prostatectomy, novel androgen receptor (AR) pathway inhibitors, such as abiraterone and enzalutamide, external beam radiotherapy (RT), brachytherapy and cryotherapy [2,3]. Further, use of new tracers for Positron Emission Tomography/Computed Tomography (PET/TC) [4,5,6,7] and novel focal therapies [8,9] have provided important advances in diagnosis, follow-up and treatment of PC patients in the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…When the clinical variables and their relation to the total cost were evaluated, it was observed that patients who did not have their primary tumor treated previously had a higher risk of presenting the outcome (high cost). It is known that the local progression of PC may result in invasion of adjacent structures, urinary retention, hematuria (bladder invasion), intestinal obstruction, and fistulas (26). These are serious complications that demand hospital care, explaining the high cost in the group with no previous local treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, little attention has been focused on the risk factors and prognosis of atypical metastases including liver, brain, and lung metastases in stage IV PCa patients. Previous studies ( 1 , 7 - 9 ) reported that visceral involvement in PCa might be correlated to worse survival outcomes. The visceral metastatic site and frequency of occurrence were described based on a large population using SEER database.…”
Section: Introductionmentioning
confidence: 91%